2017
DOI: 10.1002/bit.25949
|View full text |Cite
|
Sign up to set email alerts
|

Predictive approach for protein aggregation: Correlation of protein surface characteristics and conformational flexibility to protein aggregation propensity

Abstract: The aggregation of proteins became one of the major challenges in the development of biopharmaceu-ticals since the formation of aggregates can affect drug quality and immunogenicity. However, aggregation mechanisms are highly complex and the investigation requires cost, time, and material intensive experi-mental effort. In the present work, the predictive power of protein characteristics for the phase behavior of three different proteins which are very similar in size and structure was studied. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…There was precipitate visible by the end of each ITC titration, and the stoichiometry of inhibitor binding indicated that only 10% of the protein was able to bind ligands by the end of the titration. This was perhaps not surprising considering the conformational flexibility of the unliganded protein observed by HDX (see below) and the known connection between highly flexible peptides and susceptibility to aggregation, as well as the fact that even freshly purified DAHPS­(Phe) was previously found to be only 30% active . Protein inactivation during the titration might be expected to alter the apparent K d values; however, the fitted K d values were close to those determined by other methods, with K d,Mn = 5.3 ± 1.7 μM and K d,DAHP oxime = 3.1 ± 1.2 μM.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…There was precipitate visible by the end of each ITC titration, and the stoichiometry of inhibitor binding indicated that only 10% of the protein was able to bind ligands by the end of the titration. This was perhaps not surprising considering the conformational flexibility of the unliganded protein observed by HDX (see below) and the known connection between highly flexible peptides and susceptibility to aggregation, as well as the fact that even freshly purified DAHPS­(Phe) was previously found to be only 30% active . Protein inactivation during the titration might be expected to alter the apparent K d values; however, the fitted K d values were close to those determined by other methods, with K d,Mn = 5.3 ± 1.7 μM and K d,DAHP oxime = 3.1 ± 1.2 μM.…”
Section: Resultssupporting
confidence: 56%
“…Previously, spatially resolved hydrogen/deuterium exchange (HDX) measurements showed that DAHPS G had unusually large amounts of conformational flexibility, including stretches that are α-helices in crystal structures . This lack of well-defined structure at the surface tends to be correlated with the propensity for aggregation and denaturation, as was observed in the ITC experiments.…”
Section: Resultsmentioning
confidence: 89%
“…There are a lot of studies on interrelationships of protein flexibility, aggregation, and chemical stability. [244][245][246] Therefore, the method development for modeling protein flexibility is another important area in computeraided antibody design.…”
Section: Perspectivesmentioning
confidence: 99%
“…Aggregation propensity is directly related with protein surface hydrophobicity ( Galm et al, 2017 ). We propose that reducing the hydrophobicity of CH2 may attenuate antibody aggregation under low pH conditions.…”
Section: Discussionmentioning
confidence: 99%